Exhumation history and timing of supergene copper mineralisation in an arid climate: New thermochronological data from the Centinela District, Atacama, Chile. (25th December 2017) - Sanchez, Caroline; Brichau, Stéphanie; Riquelme, Rodrigo; Carretier, Sébastien; Bissig, Thomas; Lopez, Cristopher; Mpodozis, Constantino; Campos, Eduardo; Regard, Vincent; Hérail, Gérard; Marquardt, Carlos
Abstract: Supergene copper mineralisation (SCM) processes occur during the unroofing of porphyry copper deposits. However, the geomorphological stage during which the main mineralisation occurs is still under debate. Here, we present 24 new thermochronological data from Cenozoic intrusives and compare them with the evolution of supergene mineralisation from the Centinela Mining District in the Atacama Desert. Our results indicate a two‐step cooling path: a rapid Late Eocene exhumation followed by a slow denudation. Previously published supergene mineralisation ages cluster after the main Upper Oligocene exhumation period. Ours is the first study that establishes the relationship between exhumation and supergene processes on the scale of a single mining district. It confirms that SCM took place during pediplanation, likely a required condition for efficient SCM under arid climatic conditions, in contrast to wet tropical environments where SCM occurs during rapid relief growth but has limited preservation potential.